L’ombra de l’eunuc o el gris del clarobscur: representació terrorista i condicionants morals - Barceló Pinya, Xavier (Studia Romanica Posnaniensia, 2015)
L’ombra de l’eunuc, by Jaume Cabré (1996), presents the inner conflict of a former terrorist during Franco’s regime, and the consequences that the unsuccessful armed struggle has in his later life. The context surrounding the writing of the book is one of discredit to the concept of armed struggle as seen in democratic Spain and, in particular, in Catalonia. In contrast with that view, the author proposes a representation of the terrorist based on the individual, at a time when terrorism was a means to fight against a totalitarian governmentality, so that it consequently became partially legitimised. This recontextualization permits a re-evaluation of the violence taboo and the weakening of the Otherness barrier, thus disrupting the simplified and stereotyped perceptions of the menace and the threatened by using perspective and characterisation.